Growth enhancement of Brassica pekenis (Loor.) exposed to foliar spray of sargassum polycystum extract. - Macawaris, Aliluina Angelica D.
Sargassum polycystum extract with concentrations of 3,000 and 5,000 ppm were applied as foliar spray on Brassica pekenis on the 14th and 28th days of growth. On the 45th day, the plants were harvested and their fresh weight, number of, surface area of 2nd, 4th and 6th were taken and measured. Results showed that the 5,000 ppm extract was the better fertilizer. An interplay between the hormones-auxin, gibberrellin and cytokinin present in the extract may be responsible for the positive response of the plants when the plants were exposed to 5,000 ppm.